(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Introduction: The magnitude and severity of trauma in rural populations is well documented worldwide, leading to building of well-equipped trauma centers. However, the magnitude of such injuries in documented in Pakistan. This study sought to quantify the orthopedic trauma presenting in a rural based hospital. Methods: All patients presenting with orthopedic trauma from January 2018 to December 2020 were included in this retrospective review. Data was extracted on etiology of trauma and region involved. Data was entered and analyzed using in SPSS version 20. Results: Total of 5476 orthopedic trauma patients presented to Emergency Department. Out of these, 3824 (69.8%) were males. Most common region involved was upper limb while the most common bone involved in upper limb was radius and ulna while in lower limb was tibia fracture. There were 2044 open injuries needing early intervention along with 519 spine injuries. Conclusion: There was a huge spectrum of injuries over the period of two years. This is a wake-up call for more specialized trauma centers to be set-up to be established in rural area to decrease the load on urban health care and provide a convenient facility for the patients.